Paint It Red - A Multimethod Study of the Nudging Effect of Coloured Cycle Lanes - Fyhri, Aslak; Karlsen, Katrine; Sundfør, Hanne B. (Frontiers in Psychology, 2021)
Many countries colour their cycle lanes, but there is still a lack of research into their impact. Coloured asphalt for cyclists conveys information, and is not a legal or physical regulation of movement. Thus, it can be considered as a good example of a nudge. In transport, there are few good examples of effective nudges for improved safety or sustainability. We use a multi-method approach, with data from streets before and after they were repaved with red asphalt. Video data measured motorists’ degree of stopping in the cycle lane, motorists’ distance when driving by, and cyclists’ placement. Field surveys with cyclists (n = 1583) asked about experiences of the cycle lane. GPS data from cyclists (n=2448) was used to measure whether coloured cycle lanes resulted in an increase in cycling. Video data showed that there was not a significant decrease in the share of passing motorists who stopped in the cycle lane. There was a significant decrease in the share that stopped in the cycle lane rather than in the car lane or on the pavement. Motorists also kept a greater distance from the cycle lane after it was repaved and a greater share of cyclists chose to cycle in the cycle lane and fewer on the pavement. Survey data showed that there was a significant interaction between condition (control vs. intervention) x time (before vs. after) for increased visibility of the cycle lane, perceived safety and ease of visualization. The GPS data revealed a significant increase in cycling for the first streets to get red asphalt, but mixed results for the later streets. We also discuss potential mechanisms behind the observed effects and whether coloured cycle lanes qualify as nudging.